Detection of Ehrlichia chaffeensis in Brazilian marsh deer (Blastocerus dichotomus) - Machado, R. Z.; Duarte, JMB; Dagnone, A. S.; Szabo, MPJ (Elsevier B.V., 2006)
Ehrlichia chaffeensis was detected for the first time in blood samples from Brazilian marsh deers (Blastocerus dichotomus) captured in the marshes of Parana River in Southeast Brazil in 1998. Seven EDTA-blood samples from deers were analyzed by PCR and nested PCR for presence of Ehrlichia chaffeensis, Ehrlichia ewingii, Ehrlichia canis, Neoriickettsia risticii, Anaplasma phagocytophilum and Anaplasma marginale. Three samples showed positive reactions for E. chaffeensis and Anaplasma marginale. None contained detectable A. phagocytophilum, E. ewingii, E. canis or Neorickettsia risticii DNA. In Brazil, the wild marsh deer may be a natural reservoir of the agents that cause human monocytotropic ehrlichiosis and ruminant erythrocytic anaplasmosis. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Ehrlichia chaffeensis; Anaplasma marginale; marsh deer; PCR; nPCR; Brazil